Governing People through Risk Technology: A Case Study of Garbage Clinical Insurance in Malang, Indonesia - Nuri Ikawati; Feriana Ira Handian (Indonesian Association for Public Administration, 2017)
Garbage Clinical Insurance (GCI) by Indonesia Medika, oﬀers an innovative program to address the prevalent issues of health, a health access equality. By using garbage as a premium of the insurance scheme, it has served the poor community in Malang with the free health facilities. By elaborating governmentality theory of Foucault as a theoretical framework, this research is aimed to investigate the means used by Indonesia Medika to shape people’s behavior through insurance technology. Moreover, this study is also dedicated to contribute to the policy discourse of addressing health access inequality. Using case study as the research design, this research found that Indonesia Medika has produced a risk discourse of insurance technology as government rationality, to govern people. This was implemented through various practices of surveillance, using the body as a target of intervention. Health risk awareness is the targeted conducts upon society, the governed. Despite the wide recognition, both at the national and international level, GCI faced diﬃculties to approach local government, as the part of their strategic alliance. However, this initiative has been considered as an alternative policy in tackling poverty, by creating a certain condition, which stimulates people to govern themselves according to the end of the state.